Pengaruh Metode Diskusi Oleh Guru Pendidikan Agama Kristen Terhadap Keaktifan Belajar Siswa Kelas XII SMA Negeri 1 Balige Kabupaten Toba Tahun Pembelajaran 2023/2024 - Debby Hutabarat; Andar Gunawan Pasaribu; Wilson Simanjuntak (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The research aims to determine the positive and significant influence of the discussion method by PAK teachers on the active learning of class XII students at SMA Negeri 1 Balige for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between the discussion method by PAK teachers on the active learning of class XII students at SMA Negeri 1 Balige for the 2023/2024 academic year. This research is a regression research using Descriptive and Inferential Statistics techniques. The population of all class XII students at SMA Negeri 1 Balige who are Protestant Christians for the 2023/2024 academic year is 286 people. Random sampling (random sampling) was 15% of the total population, namely 43 people. The research instrument is a closed questionnaire. The results of the analysis requirements obtained a value of rxy=0.466>rtabel=0.301 and tcount=3.372>ttable=2.021 showing that there is a relationship between the discussion method by the Religious Education teacher and students' active learning and obtained the regression equation. Hypothesis testing obtained Fcount=11.396>Ftable=3.23, so H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence between the discussion method by PAK teachers on the learning activeness of class XII students at SMA Negeri 1 Balige for the 2023/2024 academic year of 21.71%.